Shape differences in the semitendinosus following tendon harvesting for anterior cruciate ligament reconstruction. Issue 1 (17th April 2022) - du Moulin, William; Bourne, Matthew; Diamond, Laura E.; Konrath, Jason; Vertullo, Christopher; Lloyd, David; Saxby, David J.
Abstract: Following hamstring autograft anterior cruciate ligament reconstruction (ACLR), muscle length, cross‐sectional area, and volume are reduced. However, these discrete measures of morphology do not account for complex three‐dimensional muscle shape. The primary aim of this study was to determine between‐limb semitendinosus (ST) shape and regional morphology differences in young adults following tendon harvest for ACLR and to compare these differences with those in healthy controls. In this cross‐sectional study, magnetic resonance imaging was performed on 18 individuals with unilateral ACLR and 18 healthy controls. Bilaterally, ST muscles were segmented, and shape differences assessed between limbs and compared between groups using Jaccard index (0–1) and Hausdorff distance (mm). Length (cm), peak cross‐sectional area (cm 2 ), and volume (cm 3 ) were measured for the entire muscle and proximal, middle, and distal regions, and compared between limbs and groups. Compared to healthy controls, the ACLR group had significantly ( p  < 0.001, Cohen's d  = −2.33) lower bilateral ST shape similarity and shape deviation was significantly ( p  < 0.001, d  = 2.12) greater. Shape deviation was greatest within the distal region of the ACLR (Hausdorff: 23.1 ± 8.68 mm). Compared to both the uninjured contralateral limb and healthy controls, deficits in peak cross‐sectional area and volume in ACLR group were largest in proximal ( p  < 0.001, d  = −2.52 to −1.28) and middle ( p  < 0.001, d  = −1.81 to −1.04) regions of the ST. Overall, shape analysis provides unique insight into regional adaptations in ST morphology post‐ACLR. Findings highlight morphological features in distal ST not identified by traditional discrete morphology measures. Clinical significance: Following ACLR, risk of a secondary knee or primary hamstring injury has been reported to be between 2‐to‐5 times greater compared to those without ACLR. Change in semitendinosus (ST) shape following ACLR may affect force transmission and distribution within the hamstrings and might contribute to persistent deficits in knee flexor and internal rotator strength.